2018
DOI: 10.1530/jme-17-0214
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin exerts a protective effect against premature ovarian failure in mice

Abstract: This study was designed to investigate the protective effect of curcumin against d-galactose (d-gal)-induced premature ovarian failure (POF) in mice. A mouse POF model was induced by subcutaneous injection of d-gal (200 mg/kg/day) daily for 42 days. Mice in the curcumin group received both d-gal treatment and intraperitoneal injection of curcumin (100 mg/kg/day) for 42 days. Ovarian function, oxidative stress and apoptosis were evaluated. The P, E2 and SOD levels were higher, and the FSH, LH and MDA levels wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
93
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 120 publications
(113 citation statements)
references
References 76 publications
(85 reference statements)
5
93
1
Order By: Relevance
“…It is well known that the PI3K/Akt signaling pathway plays a crucial role in the regulation of GCs growth apoptosis during follicular development [25,26]. Emerging evidence has proven activation of PI3K/Akt signaling pathway protects GCs from oxidative stress and apoptosis [27][28][29]. Interestingly, previous study has reported that catalpol promotes axonal growth via regulating miR-124 to activate PI3K/Akt/mTOR pathway in neurons after ischemia [30].…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that the PI3K/Akt signaling pathway plays a crucial role in the regulation of GCs growth apoptosis during follicular development [25,26]. Emerging evidence has proven activation of PI3K/Akt signaling pathway protects GCs from oxidative stress and apoptosis [27][28][29]. Interestingly, previous study has reported that catalpol promotes axonal growth via regulating miR-124 to activate PI3K/Akt/mTOR pathway in neurons after ischemia [30].…”
Section: Discussionmentioning
confidence: 99%
“…Western blotting analysis was performed according to previously described methods [12]. Briefly, 50 μg of total lysate obtained from ovarian tissue was subjected to 15% polyacrylamide gel electrophoresis and then transferred to a cellulose acetate membrane.…”
Section: Methodsmentioning
confidence: 99%
“…Currently, mouse models of female reproductive aging are divided into two categories: genetic mutation animal models, such as the follitropin receptor knockout animal model [4, 5] and the dioxin/aryl hydrocarbon receptor knockout animal model [6, 7]; and poison damage models, such as the 4-vinylcyclohexene diepoxide-induced female reproductive aging model [8, 9] and the D-galactose-induced female reproductive aging model [10-12]. Although these animal models show an increase in follicular consumption or even depletion, the resulting estrous cycle disorders, decreased sex hormone secretion and decrease in or loss of fertility may indicate one or more pathological states and thus do not simulate the real pathophysiological condition of ovarian aging [8, 13].…”
Section: Introductionmentioning
confidence: 99%
“…Loss of GCs with FA leads to premature depletion of ovarian reserves and POF formation. According to literature POF animal model is established with CTX [1][2][3]. The two most well-known cell death types in the FA process are apoptosis and autophagy.…”
Section: Introductionmentioning
confidence: 99%
“…The two most well-known cell death types in the FA process are apoptosis and autophagy. In addition, recently it has been suggested that paraptosis, which is a type of cell death has associated with ERS has been played a role in this process [1,4]. In this study, it was aimed to establish the POF model in C57BL/6 female mice that was induced by CTX and evaluation of apoptosis, autophagy and paraptosis via indirect IHC method in order to determine the CDM that play a role in FA process.…”
Section: Introductionmentioning
confidence: 99%